Diagnosis and treatment of Guillain-Barré Syndrome in childhood and adolescence: An evidence- and consensus-based guideline. (March 2020) - Korinthenberg, R.; Trollmann, R.; Felderhoff-Müser, U.; Bernert, G.; Hackenberg, A.; Hufnagel, M.; Pohl, M.; Hahn, G.; Mentzel, H.J.; Sommer, C.; Lambeck, J.; Mecher, F.; et al.
Abstract: This evidence- and consensus-based practical guideline for the diagnosis and treatment of Guillain-Barré Syndrome (GBS) in childhood and adolescence has been developed by a group of delegates from relevant specialist societies and organisations; it is the result of an initiative by the German-Speaking Society of Neuropediatrics (GNP), and is supported by the Association of Scientific Medical Societies (AWMF, Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften). A systematic analysis of the literature revealed that only a few adequately-controlled studies exist for this particular age group, while none carries a low risk of bias. For this reason, the diagnostic and therapeutic recommendations largely rely on findings in adult patients with GBS, for which there are a higher number of suitable studies available. Consensus was established using a written, multi-step Delphi process. A high level of consensus could be reached for the crucial steps in diagnosis and treatment. We recommend basing the diagnostic approach on the clinical criteria of GBS and deriving support from CSF and electrophysiological findings. Repetition of invasive procedures that yield ambiguous results is only recommended if the diagnosis cannot be ascertained from the other criteria. For severe or persistently-progressive GBS treatment with intravenous immunoglobulin (IVIG) is recommended, whereas in cases of IVIG intolerance or inefficacy we recommended treatment with plasmapheresis. Corticosteroids are ineffective for GBS but can be considered when acute onset chronic inflammatory demyelinating polyneuropathy (A-CIDP) is suspected due to a prolonged disease course. The full German version of the Guideline is available on the AWMF website (https://www.awmf.org/leitlinien/detail/ll/022-008.html ). Highlights: Diagnosis of GBS should be based on clinical course, distribution of weakness, typical electrophysiology and CSF-findings. Painful diagnostic procedures should only be repeated if this is necessary for a clear diagnosis and treatment indication. High-dose IVIG or plasma-exchange is the treatment modality of first choice proven with a satisfactory Level of Evidence. Apparent non-responders have to be treated on individual decisions depending on details of the clinical course. Combined rehabilitation procedures are necessary for all patients with significant disability.